Amy L. Hubbell. Remembering French Algeria: Pieds-Noirs, Identity, and Exile. Lincoln and London: U of Nebraska P, 2015. - Anna Rocca (Studies in 20th & 21st Century Literature, 2017)
Review of Amy L. Hubbell. Remembering French Algeria: Pieds-Noirs, Identity, and Exile. Lincoln and London: U of Nebraska P, 2015.
Keywords: Pieds-Noirs; Memory; Trauma; Collective Amnesia; Algeria/France.